Quantum optics with one or two photons - Sahar Basiri Esfahani (Proceedings of the Royal Society A: Mathematical, Physical and Engineering Science, 2015)
We discuss the concept of a single-photon state together with how they are generated, measured and interact with linear and nonlinear systems. In particular, we consider how a single-photon state interacts with an opto-mechanical system: an optical cavity with a moving mirror and how such states can be used as a measurement probe for the mechanical degrees of freedom. We conclude with a discussion of how single-photon states are modified in a gravitational field due to the red-shift.